Qualitative assessment of surface water using the CWQI method and with the Aquachem software (Case study: Qaen River in South Khorasan) - Fahimeh Khadempour; Ali Shahidi (Mashhad University of Medical Sciences, 2017)
Introduction: Qualitative assessment of water resources using qualitative indicators as one of the most suitable methods for managing water areas and having a regular program for water quality protection and pollution prevention is necessary. Subject & method: The use of the CWQI index to identify the country's water resources (especially lakes and rivers) can be a good tool. In this study, water quality was evaluated in two ophthalmic stations of Oliyakhonic and Farokhi in the Gain river basin of southern Khorasan province during the years of 2007-2016 with the use of this indicator and Aquachem software. In this study, parameters of calcium, magnesium, potassium, sodium, chloride, sulfate, electrical conductivity and acidity were used. Results: The CWQI index for agricultural consumption has been decreasing from the upstream downstream, which may be due to increased water salinity in the downstream direction or the flow of agricultural, industrial and urban wastewater (household and industrial waste). The level of pollution and the concentration of undesirable factors rises from the upstream and downstream, and undesirable water quality for fish life, so that most stations require purification for aquaculture. Conclusion: Both stations are in bad rank for drinking, aquatic, irrigation and livestock. Also, for both recreation both stations were in high rank. Also, according to the Piper diagram, the type and the water facies are bicarbonate-magnesium-calcium.